2007
DOI: 10.3748/wjg.v13.i47.6356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quantitative contrast harmonic imaging to assess malignancy of liver tumors: A prospective controlled two-center study

Abstract: AIM:To e s t a b l i s h t h e e x t e n t t o w h i c h c o n t ra s t enhancement with SonoVue in combination with quantitative evaluation of contrast-medium dynamics facilitates the detection of hepatic tumors. METHODS:One hundred patients with histologically confirmed malignant or benign hepatic tumor (maximum size 5 cm) were analyzed. Contrast-enhanced ultrasound (bolus injection 2.5 mL SonoVue) was carried out with intermittent breath-holding technique using a multifrequency transducer (2.5-4 MHz). Nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Jung et al 74 investigated 100 patients with histologically confirmed liver tumors (59% malignant). Time-intensity curve analysis after dynamic contrast-enhanced US imaging with SonoVue resulted in sensitivity of 98% and specificity of 90% for diagnosis of malignancy by analyzing the behavior of the lesions in the late phase.…”
Section: Potential Of Dynamic Contrast-enhanced Us As An Instrument Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al 74 investigated 100 patients with histologically confirmed liver tumors (59% malignant). Time-intensity curve analysis after dynamic contrast-enhanced US imaging with SonoVue resulted in sensitivity of 98% and specificity of 90% for diagnosis of malignancy by analyzing the behavior of the lesions in the late phase.…”
Section: Potential Of Dynamic Contrast-enhanced Us As An Instrument Tmentioning
confidence: 99%
“…In animals, it has been demonstrated that tumor characterization and differentiation of benign from malignant tumors are possible by replenishment kinetics. 25,68 Also, in human studies, differentiation between benign and malignant tumors in parenchymatous organs (liver tumors, 35,52,54,74 pancreatic masses, 44,53 lymph nodes ,51,59 breast tumors, 33,34,37,60 prostate nodules, 45,55,58,61,63 adrenal masses, 40 urinary bladder masses, 36 adnexal masses, 50,56 glioblastomas, 75 soft tissue tumors, 76 and thyroid nodules 32 ) could be achieved with dynamic contrastenhanced US and time-intensity curve analysis.…”
Section: Differentiation Of Benign and Malignant Tumorsmentioning
confidence: 99%
“…1 Several authors propose this late phase enhancement to differentiate benign from malignant lesions. 5,6,8,10,[14][15][16][17] The evaluation of early phase enhancement, however, is particularly important for improved specificity especially in a study population which comprised a majority of hypervascular lesions.…”
Section: Contrast-enhanced Us Of Focal Liver Lesionsmentioning
confidence: 99%
“…For patients with multiple lesions, only up to three lesions can be distinctly targeted and studied throughout all vascular phases of CEUS because of limited arterial phase time window as a result of rapid contrast uptake and washout of most hypervascular lesions. 8 The detection of additional lesions, especially those that exhibit predominantly arterial enhancement such as HCC, represents another intrinsic limitation of CEUS.…”
Section: Contrast-enhanced Us Of Focal Liver Lesionsmentioning
confidence: 99%
See 1 more Smart Citation